Identifying inhibitors/enhancers of quantitative real-time PCR in food samples using a newly developed synthetic plasmid - Sovová, Tereza; Křížová, Barbora; Hodek, Jan; Ovesná, Jaroslava (Journal of the science of food and agriculture, 2016)
BACKGROUND: Polymerase chain reaction (PCR) has become a common technique offering fast and sensitive analysis of DNA in food/feed samples. However, many substances, either already present in the sample or introduced during sample processing, inhibit PCR and thus underestimate the DNA content. It is therefore necessary to identify PCR inhibition in order to correctly evaluate the sample. RESULTS: We designed and validated a synthetic plasmid DNA that can be used to detect and quantify PCR inhibition. The DNA sequence, appropriate primers and probe, were designed in silico, synthesized and the sequence was inserted into a plasmid vector. The performance of the plasmid was verified via calibration curves and by performing the assay in the presence of various DNAs (crops, fungus, bacterium). The detection of PCR inhibition was assessed using six inhibiting substances with different modes of action, substances used in sample processing (EDTA, ethanol, NaCl, SDS) and food additives (sodium glutamate, tartrazine). The plasmid performance proved to be reproducible and there were no interactions with other DNAs. The plasmid was able to identify the presence of the inhibitors in a wide range of concentrations. CONCLUSION: The presented plasmid DNA is a suitable and inexpensive possibility for evaluating PCR inhibition.
Keywords: plasmid DNA; food quality; food additives; PCR inhibition; DNA Primers; lidé; Plasmids; kvantitativní polymerázová řetězová reakce; geneticky modifikované rostliny; plazmidy; Sensitivity and Specificity; DNA primery; Plants, Genetically Modified; senzitivita a specificita; Real-Time Polymerase Chain Reaction; Humans